Hyaluronan-Based Nanofibers: Fabrication, Characterization and Application - Snetkov, Petr (Polymers (Basel), 2019)
Nano- and microfibers based on biopolymers are some of the most attractive issues of biotechnology due to their unique properties and effectiveness. Hyaluronan is well-known as a biodegradable, naturally-occurring polymer, which has great potential for being utilized in a fibrous form. The obtaining of fibers from hyaluronan presents a major challenge because of the hydrophilic character of the polymer and the high viscosity level of its solutions. Electrospinning, as the advanced and effective method of the fiber generation, is difficult. The nano- and microfibers from hyaluronan may be obtained by utilizing special techniques, including binary/ternary solvent systems and several polymers described as modifying (or carrying), such as polyethylene oxide (PEO) and polyvinyl alcohol (PVA). This paper reviews various methods for the synthesis of hyaluronan-based fibers, and also collects brief information on the properties and biological activity of hyaluronan and fibrous materials based on it.